Genome-Wide Mutation Rate Response to pH Change in the Coral Reef Pathogen Vibrio shilonii AK1 - Chloe Strauss (American Society for Microbiology, 2017)
ABSTRACT Recent application of mutation accumulation techniques combined with whole-genome sequencing (MA/WGS) has greatly promoted studies of spontaneous mutation. However, such explorations have rarely been conducted on marine organisms, and it is unclear how marine habitats have influenced genome stability. This report resolves the mutation rate and spectrum of the coral reef pathogen Vibrio shilonii, which causes coral bleaching and endangers the biodiversity maintained by coral reefs. We found that its mutation rate and spectrum are highly similar to those of other studied bacteria from various habitats, despite the saline environment. The mutational properties of this marine bacterium are thus controlled by other general evolutionary forces such as natural selection and genetic drift. We also found that as pH drops, the mutation rate decreases and the mutation spectrum is biased in the direction of generating G/C nucleotides. This implies that evolutionary features of this organism and perhaps other marine microbes might be altered by the increasingly acidic ocean water caused by excess CO2 emission. Nonetheless, further exploration is needed as the pH range tested in this study was rather narrow and many other possible mutation determinants, such as carbonate increase, are associated with ocean acidification. IMPORTANCE This study explored the pH dependence of a bacterial genome-wide mutation rate. We discovered that the genome-wide rates of appearance of most mutation types decrease linearly and that the mutation spectrum is biased in generating more G/C nucleotides with pH drop in the coral reef pathogen V. shilonii.